Effect of gold nanoparticle shape on the photophysicochemical properties of sulphur containing metallophthalocyanines - Dube, Edith; Nyokong, Tebello (Journal of Molecular Structure, 2020)
In this work tetrakis–[(thiopheneethoxy) phthalocyaninato] zinc(II) (1), tetrakis–[(thiopheneethoxy) phthalocyaninato] indium (II) chloride (2), tetrakis [(benzo [d]thiazol-2-yl phenoxy) phthalocyaninato] zinc(II) (3), and tetrakis [(benzo [d]thiazol-2-yl phenoxy)phthalocyaninato] indium (II) chloride (4) were linked to both gold nanospheres (AuNSs) and gold nanotriangles (AuNTs) via Au-S and Au-N (the latter for complexes 3 and 4 only) self assembly. The photophysicochemical behaviour of complexes and their conjugates were studied. The conjugates yielded improved triplet and singlet quantum yields, with nanospheres displaying better properties than nanotriangles. The conjugates with a benzothiazole phenoxy substituent also yielded better properties than their thiophene ethoxy counterpart. These conjugates especially those with a benzothiazole phenoxy substituent have potential as photosensitisers for photodynamic therapy applications.